Recommendations for the Integration of Traditional and Local Knowledge into the Work of the Arctic Council. - Sustainable Development Working Group (SDWG) (Sustainable Development Working Group (SDWG), 2015)
Recommendations for the Integration of Traditional and Local Knowledge into the Work of the Arctic Council, delivered by the Arctic Council Sustainable Development Working Group (SDWG) at the Arctic Council's 9th Ministerial Meeting in Iqaluit, Canada, April 24-25 2015.